2007
DOI: 10.1097/gim.0b013e318149e354
|View full text |Cite
|
Sign up to set email alerts
|

Array-based comparative genomic hybridization: clinical contexts for targeted and whole-genome designs

Abstract: Array-based comparative genomic hybridization is ushering in a new standard for analyzing the genome, overcoming the limits of resolution associated with conventional G-banded karyotyping. The first genomic arrays were based on bacterial artificial chromosome clones mapped during the initial phases of the Human Genome Project. These arrays essentially represented multiple fluorescence in situ hybridization assays performed simultaneously. The first arrays featured a targeted design, consisting of hundreds of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…[31][32][33] Some efforts have been made to develop explicit guidelines for clinical uptake of array-based molecular cytogenetics. 34,35 They currently suggest that whole genome analysis not be employed as a firstpass technology in cytogenetic analysis. However, they also note that the main issue is interpretation of findings, given that array methods routinely detect multiple CNVs even in patients without a clear medical ascertainment.…”
Section: Novel Genetic Analysismentioning
confidence: 99%
“…[31][32][33] Some efforts have been made to develop explicit guidelines for clinical uptake of array-based molecular cytogenetics. 34,35 They currently suggest that whole genome analysis not be employed as a firstpass technology in cytogenetic analysis. However, they also note that the main issue is interpretation of findings, given that array methods routinely detect multiple CNVs even in patients without a clear medical ascertainment.…”
Section: Novel Genetic Analysismentioning
confidence: 99%
“…[27][28][29] The approach described here easily lends itself to future expansion that will blur the distinctions between focused and nonfocused arrays by allowing many options for array design and analysis.…”
mentioning
confidence: 99%
“…In addition to showing the superior analytical sensitivity of oligonucleotide arrays compared with BAC arrays, these studies also demonstrated the convenience of oligonucleotide-array design and manufacturing. Aradhya and Cherry used samples from 20 patients with dysmorphic features, developmental delay, or mental retardation to directly compare the performance of whole-genome BAC arrays of 1-Mb resolution (Spectral Chip 2600; PerkinElmer) with that of Agilent whole-genome oligonucleotide CGH arrays of 35-kb resolution (33 ). All of these patients had a typical karyotype.…”
Section: Individuals With Oligonucleotide Arraysmentioning
confidence: 99%